TEORI KONTINGENSI, SISTEM PENGENDALIAN MANAJEMEN DAN KELUARAN PERUSAHAAN: HASIL YANG LALU DAN ARAH MASA DEPAN (STIE YPPI Rembang, 2013)
AbstractContingency theory arose in response to a universal approach which states that the optimal control design was acceptable to all regulatory and company. System contingency form an unbroken circle of implications and affect each other. Contingency factor is determined by the managers decision, and the factors - other factors determined in accordance with the external conditions. Organizations choose Diman market there is competition and strategy is done. One of the difficulties in studying Management Control Systems is the presence of ambiguity and contradictions in defining the control system. In addition, this type of control used by the corporate structure, corporate culture, and human resources, both include hiring, training, and personnel reduction policies.Keywords: contingency theory, control systems